2004
DOI: 10.1001/archpsyc.61.9.933
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Investigation of Stress Inoculation in Young Monkeys

Abstract: These results provide the first prospective evidence that moderately stressful early experiences strengthen socioemotional and neuroendocrine resistance to subsequent stressors. This preclinical model offers essential opportunities to improve our understanding and enhance prevention of human stress-related psychiatric disorders by elucidating the etiology and neurobiology of stress resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
144
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(159 citation statements)
references
References 64 publications
14
144
1
Order By: Relevance
“…One intriguing finding to emerge from this retrospective research has been that stress resistance is associated with childhood exposure to mildly stressful events (1,3). Prospective longitudinal studies of nonhuman primates support this finding, because monkeys exposed to brief, 1-h periods of maternalseparation stress exhibit diminished anxiety and attenuated hypothalamic-pituitary-adrenal (HPA)-axis responses to subsequent stressors compared with unmanipulated monkeys (4).…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…One intriguing finding to emerge from this retrospective research has been that stress resistance is associated with childhood exposure to mildly stressful events (1,3). Prospective longitudinal studies of nonhuman primates support this finding, because monkeys exposed to brief, 1-h periods of maternalseparation stress exhibit diminished anxiety and attenuated hypothalamic-pituitary-adrenal (HPA)-axis responses to subsequent stressors compared with unmanipulated monkeys (4).…”
mentioning
confidence: 76%
“…Blood samples were also collected immediately after testing to examine cortisol levels after novelty exposure, and a subset of these data was reported in ref. 4. All blood samples were collected between 1530 and 1800 h to control for circadian variation (37).…”
Section: Methods Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, limited exposure may ''toughen" individuals, leaving them more emotionally stable and better able to cope with both difficult stressors and minor challenges; in contrast, both sheltering from all stressors and exposure to continuous chronic stressors lead to lack of ''toughness" [10]. Notably, previous research has ignored the potential protective effects of lifetime adversity on CBP patients' responses to their pain [5,22,35].…”
Section: Introductionmentioning
confidence: 99%
“…Research in rodents supports the stress inoculation hypothesis and has suggested that this protection against some of the later negative effects may be due to neuroplasticity in the PFC induced by stress inoculation (Southwick and Charney, 2012). In one study, young monkeys were presented with a controllable stressor (periodic short maternal separations) over a course of 10 weeks (Parker et al, 2004). These monkeys experienced acute stress during the separation periods, illustrated by agitation as well as temporary increased levels of cortisol.…”
Section: Developmental Factors In Resiliencementioning
confidence: 99%